Antibacterial of Endophytic Bacteria from Papaya (Carica papaya) Seeds Againts Staphylococcus aureus and Escherichia coli - Pratiwi, Esti Rizkiana; Al Batati, Nadiah; Firamadhani, Nuzzulul Anisa (Jurnal Biologi Tropis, 2024)
Endophytic bacteria were produce antibacterial compounds from various plants has been widely reported as considered efficient in overcoming resistant pathogen infections. This study aims to obtain endophytic bacteria from papaya seeds which can produce antibacterials. Papaya seeds were used to isolate endophytic bacteria, which were then examined for antibacterial activity. The dics diffusion method is used to determine the antibacterial activity's efficacy against Escherichia coli and Staphylococcus aureus. There are nine isolates of endophytic bacteria in all. According to a potency test, the nine isolates exhibit strong antibacterial activity against Escherichia coli and Staphylococcus aureus, respectively. Every isolate has the ability to effectively inhibit Staphylococcus aureus. The only isolates that could suppress Escherichia coli were CPA 5, CPA 6, and CPA 8. Based on their antibacterial activity against Escherichia coli and Staphylococcus aureus, it was determined that the endophytic bacterial isolates from papaya seed have the capacity to generate antibacterials.